?MINERAL ACID EFFECT ON THE TRACE ELEMENT DETERMINATION IN LICHEN CERTIFIED REFERENCE MATERIAL AND ALGAE BY INDUCTIVELY COUPLED PLASMA TOMIC EMISSION SPECTROMETRY - Bamiro, F kJ; Benzo, Z; Schorin, H; Marcano, E; Gomez, C (Biological Sciences - PJSIR, 2000)
A study has been made or mineral acid matrix interferences in trace element determinations and methods are described for the multi-element analysis of lichen and algae (blcmonitors) using Inductively Coupled Plasma Emission Spectrometry (ICP-AES). Several calibration strategies were compared employing aqueous standards with and without acids using modified rcp instrumental parameters. There was marked depression in analyte signal intensity in all the measurements. It has been shown that signal depressions of up to 32% can be observed under normal operating conditions. The use ofacid matrix-matched standards and internal standard for calibrations substantially reduced signal depression problem. The methods gave elemental recovery from 97.7 to 98.8%. The accuracy otthc methods was assessed by anaiysing the certi- fied lichen material from the International Atomic Energy Agency (IAEA). Accurate results were obtained by using the above calibration strategy with improved precision.